Síntese e caracterização de nanopartículas de maguemita recobertas com sílica funcionalizada com grupos amina - ALMEIDA, Michelly Patrícia Santana de (2008)
Magnetic nanoparticles coated with several kinds of materials have been the focus of intense research due to their potential applications in biomedicine. This type of material contains a magnetic core that is involved by a shell of different composition. The coating of magnetic nanoparticles with amino-functionalized silica is particularly important because of its reactivity which allows the coupling with biological molecules such as fragments of DNA, antibodies, proteins, among others. In this work, maghemite nanoparticles were coated with silica and with amino-functionalized silica, the incorporation of them being achieved by using tetraethoxysilane (TEOS) and aminopropyltrimethoxysilane (APTS) as the precursors of the sol-gel system. Firstly, the magnetic fluids of maghemita were prepared and afterwards they were employed in the silica-coating procedures which were based on the Stöber method. Some experimental parameters were varied, such as the number of maghemita nanoparticles, pH of the reaction medium, time of reaction and amount of TEOS, with the aim of modulating the characteristics of the solids and obtaining stable aqueous suspensions of the materials. All products were analyzed by the following techniques: X- ray diffraction, diffuse reflectance infrared spectroscopy, dynamic light scattering, electrophoretic mobility (zeta potential) and transmission electron microscopy.